Case Report: Hypertension in Pregnancy - Widad, Alfaniah Aufa Shidqi Al; Susetyo, Budi; Hidayat, Fadil (CV. Publikasi Indonesia, 2025)
Hypertensive disorders in pregnancy, such as preeclampsia, are a leading cause of maternal and perinatal morbidity and mortality. This case report details the management of a patient with severe preeclampsia, highlighting the challenge of a progressive hemoglobin drop without thrombocytopenia. The report aims to describe the clinical presentation, diagnostic approach, and management of a term pregnancy complicated by severe preeclampsia and a suspected concurrent urinary tract infection. A case study was conducted on a 23-year-old woman, G2P1A0, at 39 weeks’ gestation, who presented in the active phase of labor with hypertension and bleeding. Data were collected through clinical examination, laboratory tests, and monitoring of the implemented treatment regimen. The patient was diagnosed with severe preeclampsia based on hypertension (160/100 mmHg) and proteinuria (2+). Laboratory findings revealed a significant drop in hemoglobin (from 11.4 g/dL to 8.2 g/dL) with normal platelet counts, ruling out HELLP syndrome, alongside leukocytosis and nitrite positivity suggesting a urinary tract infection. Management with a combination of magnesium sulfate, nifedipine, oxytocin, and antibiotics successfully stabilized maternal hemodynamics. This case underscores the importance of vigilant monitoring for atypical presentations such as progressive anemia in preeclampsia and affirms the effectiveness of a combined MgSO₄–nifedipine regimen, alongside infection control and timely delivery, in managing severe preeclampsia at term.